Study of Drug Use in Essential Hypertension and Their Compliance - Joshi, Mili; Rao, B.S.; Khan, G.M. (Kathmandu University Journal of Science, Engineering and Technology, 2006)
Hypertension (HTN) Affects Approximately 1 Billion People Worldwide. The Prevalence of HTN Increase with Age and Even Further Unless Broad and Effective Preventive Measures Are Implemented. Significant Age, Obesity, Lifestyle, Smoking and Alcohol Use Related Factors in Prevalence of Essential HTN Were Seen. The Use of Drugs Was Observed Related to Different Factors. Out of Total 156 Patients, the Distribution of Antihypertensive Agents (AHA) Used Were Calcium Channel Blockers (65%), Beta Blockers (52%), Angiotensin Converting Enzyme Inhibitors (19%), Diuretics (28%) and Angiotensin Receptor Blockers (9%). Among Individual Drugs, 102 Patients Were on Amlodepine, 39 on Hydrochlorthiazide, 82 on Atenolol, 14 on Losartan, and 30 Subjects Were on Enalapril. With Respect to Overall Utilization, Calcium Channel Blockers (Amlodepine) Were Observed to Be the Most Frequently Prescribed AHAs, Beta Blockers (Atenolol) Ranked Second Followed by Angiotensin Converting Enzyme Inhibitors (Enalapril), Angiotensin Receptor Blockers (Losartan) and Diuretics (Hydrochlorothiazide). Within Each Class of AHA Used the Most Frequently Used Were Calcium Channel Blockers, (Amlodepine- 97.14% and Nefidipine- 2.86%) Followed by Beta Blockers (Atenolol 97.6% and Metoprolol 2.4%, Angiotensin Converting Enzyme Inhibitors (Enalapril 96.77% and Lisinopril 3.23%), Diuretics (Hydrochlorthiazide 88.63 %and Loop Diuretics 11.35%), Angiotensin Receptor Blockers (Losartan). Both in Monotherapy and Combination Therapy, the Most Preferred AHA Remains Amlodepine. In Combination Therapy, the Most Extensively Used Combination Was Amlodepine with Atenolol. Calcium Channel Blockers Were Appropriately Prescribed in Significant Number of Patients Above 50 Years. Angiotensin Receptor Blockers Account for a Very Small Proportion of Drug Use Profile, Which May Be Due to the High Cost and Lower Availability of These Drugs. The General Pattern of Antihypertensive Agent Utilizations Appears to Be Within the Recommendation of British HTN Society Guidelines